Introduction of Superior Feed Forage to Improve Feed Nutrition and Livestock Productivity in the “Sekar Pasti Wangi” Livestock Farmer Group, Petiga Village, Marga District, Tabanan Regency - Suwitari, Ni Ketut Etty; Ni Ketut Sri Rukmini; Luh Suariani (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2022)
The partner in implementing this PKM (Community service) is the Sekar Pasti Wangi Livestock Group located in Banjar Seminyak Petiga Village, Marga District, Tabanan Regency. This group raises 20 cows with 19 members. Partners have problems not having information about superior types of animal feed forage, understanding and skills regarding feed forage cultivation technology and how to feed livestock. With this understanding and skills, it will be able to increase the nutritional content contained in the feed both in quality and quantity which has an impact on increasing livestock production. The goal to be achieved is to provide an understanding of nutrition in applying forage cultivation technology as animal feed that can take place evenly throughout the year. The Sekar Pasti Wangi Livestock Farmer Group already knows some superior forage, mastering its cultivation technology, ration formulation and understanding and understanding the nutritional needs of cows. Mastery of technology is almost 80%, so it is necessary to provide assistance again to the group at the time of the first, second slaughter and forage treatment of feed and serving techniques so that forage remains of good quality. From the community partnership program that we carry out, it can be concluded that partners know the types of feed forage by 80%. In addition, there is an increase in livestock productivity of 0.3-0.4 kg / head / day can be seen from the growth performance, so it is expected that partner income will increase.